P1507 Early and late morphological changes in the athlete"s heart: a longitudinal cohort study in young elite athletes. (17th January 2020) - Bjerring, A W; Landgraff, H E W; Leirstein, S; Lihagen, M; Skei, M; Murbraech, K; Brun, H; Stokke, T M; Haugaa, K H; Hallen, J; Edvardsen, T; Sarvari, S I
Abstract: Funding Acknowledgements: South-Eastern Norway Regional Health Authority OnBehalf: Center for Cardiological Innovation Background: Recent studies have suggested an initial concentric remodelling in the early development of the athlete's heart in endurance athletes. However, the development from the early to the fully developed endurance athlete's heart has not been described in longitudinal studies. Aims: This study aims to explore the morphological changes occurring in hearts of young endurance athletes transitioning through adolescence. Methods: Forty-eight cross-country skiers were examined at age 12 (12.1 ± 0.2 years) and then again at age 15 (15.3 ± 0.3 years). Cardiopulmonary exercise test and echocardiography, including 3D acquisitions, was performed in all subjects at both baseline and follow-up. Results: At follow-up, 31 (65%) of the endurance athletes were still active and 17 (35%) were not. No differences in cardiac morphology were identified at baseline. At 15 years of age, the active endurance athletes had greater VO2 max, 3D indexed left ventricular end-diastolic and end-systolic volumes (Table). Relative wall thickness (RWT) decreased in the active endurance athletes during follow-up (0.35 ± 0.05 to 0.31 ± 0.04, p < 0.001), but not in the former athletes. Four active endurance athletes had RWT above the upper reference values at baseline; at follow up, all had normalized. Conclusion: After an early concentric remodeling in the 12 years old athletes, those who continued regular endurance training developed eccentric changes with chamber dilatation and a drop in RWT. In contrast, those who ceased endurance training maintained a comparable wall thickness, but did not develop chamber dilatation nor experience a drop in RWT.